Effect of a stylet on specimen sampling in thyroid fine needle aspiration: A randomized, controlled, non-inferiority trial - Luo, Pengfei; Mu, Xiali; Ma, Wei; Jiao, Dahai; Zhang, Peixin (Frontiers in Endocrinology, 2023)
Background There is a cost advantage in using a needle without stylet over a needle with stylet in thyroid fine needle aspiration (FNA). This study aimed to elucidate the non-inferiority of thyroid FNA without a stylet (S-) to thyroid FNA with a stylet (S+) on specimen sampling. Methods In this study, patients with thyroid nodules undergoing FNA were consecutively enrolled between May 2022 and July 2022. One experienced operator performed two punctures of each nodule with a stylet and without a stylet. Specimen adequacy was the primary outcome. Wald test was used for statistical analysis of the primary outcome. The difference in specimen adequacy between the two methods was expressed as a two-sided 95% confidence interval (CI). The S- method was considered non-inferior to the S+ method if the lower bound of the 95% CI of the S- minus S+ adequacy difference was greater than a predetermined non-inferiority margin of -10%. Results A total of 149 patients (195 nodules) were enrolled in the study. A total of 167 of 195 nodules (85.64%) and 169 of 195 nodules (86.67%) were obtained adequate specimens using the S+ and S- methods, respectively. The difference in specimen adequacy (S- minus S+) between the two methods was 1.03% (95% CI, -5.83% to 7.88%). The lower bound 95% CI of the difference in specimen adequacy (-5.83%) was greater than the predetermined non-inferiority margin of -10%. The difference in the yield for malignancy was not significantly different between the two methods. Conclusion Thyroid FNA without a stylet is non-inferior to thyroid FNA with a stylet on specimen sampling.